Egr1 mediates retinal vascular dysfunction in diabetes mellitus via promoting p53 transcription. Issue 5 (19th March 2019) - Ao, Haocheng; Liu, Bingqian; Li, Haichun; Lu, Lin
Abstract: Objectives: This study focused on investigating the expression and underlying molecular mechanism of early growth response 1 ( Egr1 ) in diabetic retinopathy. Methods: A microarray assay was applied to examine differentially expressed genes in the retina tissues of normal rats, as well as in those of streptozotocin‐induced diabetic rats. Human retinal vascular endothelial cells (HRVECs) transfected with sh‐NC, sh‐ Egr1 or sh‐ Egr1 + pVax1‐p53 were cultured under high‐glucose conditions and then used to explore the role of Egr1 in vitro. The effect of Egr1 on retinal vascular dysfunction caused by diabetes was examined by sh‐ Egr1 administration in vivo Results: Early growth response 1 was found to be up‐regulated in the retinas of diabetic rats compared to those of normal rats. Down‐regulation of Egr1 in HRVECs under high‐glucose conditions inhibited the apoptosis, migration and tube formation in vitro. Moreover, sh‐ Egr1 partially reduced the injurious effects of hyperglycaemia on retinal vascular function by decreasing apoptotic cells and microvascular formation in vivo. The reduction of Egr1 evidently down‐regulated the p53 expression. Overexpression of p53 rescued the inhibition of sh‐ Egr1 in HRVECs under high‐glucose concentration on apoptosis, migration and tube formation in vitro. Conclusion: Down‐regulation of Egr1 partially reduced the injurious effects of hyperglycaemia on retinal vascular function via inhibiting p53 expression.